PENGENDALIAN WAKTU DAN BIAYA MENGGUNAKAN EARNED VALUE CONCEPT PADA PROYEK PEMBANGUNAN JALUR GANDA REL KERETA API LINTAS SELATAN JAWA MOJOKERTO-SEPANJANG - Damarhuda Afdholi Martin; Budi Witjaksana (LPPM Universitas Bina Bangsa, 2023)
The train flow between Mojokerto - Along the South Cross of Java, which is now only Single Tracking, is a train operation line that is heavy with traffic so that there are often delays in train travel. During the implementation of the Mojokerto-Sepanjang double-track railway construction project in week 43 – week 53, there was a schedule discrepancy in the field work with what had been planned, which could eventually result in time delays and cost overruns for project completion. From the existing background, the problem found is how is the performance of time and cost in the Mojokerto-Along Railway Double Line Construction project (Package 9)? The results of research using the Earned Value method in weeks 43 to 53 are CPI values < 1, this shows that the cost of implementing the work is greater than budgeted, so that the estimated cost of the project to be completed is IDR 53,236,370,349,979, Which means here the project suffers losses in terms of cost. Meanwhile, in terms of time in week 43, the SPI value > 1, meaning that time performance is on schedule or even ahead of plan. While in week 44 to week 53 the SPI value < 1, This means that the project is experiencing delays from the planned schedule. The calculation of the EAS value in week 53 results in the estimated project completion time of 853,993 days or 122 weeks, meaning that the project is delayed from the planned schedule